PERLINDUNGAN HUKUM TERHADAP ATLET PENCAK SILAT YANG MENGALAMI CIDERA ATAU KEMATIAN SAAT BERLAGA - Dian Tri Asmoro; Ridho Sa’dillah Ahmad (JUNAGARA: Jurnal Ilmiah Hukum dan Kenegaraan, 2024)
The issue of legal protection for athletes has become a serious concern in Indonesia, particularly with the increasing cases of minor to severe injuries experienced by athletes. This research focuses on Pencak Silat athletes who suffer severe injuries or death during competitions. The study employs an empirical method with a case study approach, followed by juridical analysis. Factors contributing to the death of athletes include the non-fulfillment of rules and procedures in Pencak Silat competitions, such as committee rules, match duration, field rules, referee regulations, and competition equipment. This research emphasizes the importance of regulations that provide legal protection for athletes, such as Law No. 3 of 2005 on the National Sports System, which regulates the rights and obligations, as well as the authority and responsibility of all parties related to sports. This law aims to provide legal certainty for the government, local governments, and the public in sports activities, in order to create an accomplished society and nation